Rachael Ray's look + cook : 100 can't-miss main courses in pictures - Ray, Rachael (Clarkson Potter, 2010)
Celebrity cook Rachael Ray presents new recipes, each featuring beautiful and helpful step-by-step full-color photographs that illustrate how to create each meal, along with photographs of the finished dishes. Also includes 125 bonus, never-before-published recipes, including 30-minute meals, meals for kids, sides and starters, simple sauces, bottom-of-the-jar tips, and desserts.